Causes of the Abrupt and Sustained 2016–2023 Antarctic Sea‐Ice Decline: A Sea Ice–Ocean Model Perspective - K. Kusahara; H. Tatebe (Geophysical Research Letters)
Abstract Antarctic sea ice, which undergoes large seasonal changes and plays a crucial role in the global climate system, showed a gradual increasing trend in its extent from the late 1970s to 2015 but experienced a sharp decline in 2016, followed by record lows in subsequent years. This study investigates the causes of the recent regime shift in Antarctic sea‐ice extent (SIE) using a global sea ice–ocean model with 0.25° resolution forced by atmospheric reanalysis‐based surface boundary conditions. Numerical experiments reveal that thermodynamic boundary conditions, particularly the increased subpolar sea surface temperatures (SSTs) north of the sea‐ice edge, are the dominant drivers of Antarctic sea‐ice decline. Additionally, wind stress partly contributes to the variability in summer SIE. These findings highlight that SST warming near the sea‐ice edge, resulting from atmosphere–ocean interactions under ongoing atmospheric warming, plays a key role in the recent decline in Antarctic SIE.